Optimizing apple juice extraction in multiple presses - Gonzalez, Maria Teresa (2000)
A method was developed to find the optimum hydration flow sheet that maximizes either the profit or the soluble solids recovery for a given number of presses in an apple concentrate juice plant. The pomace arising from a press can be wetted with either pure water or dilute juice from downstream presses, or a mixture of both in any proportion. The mass balance around the presses involving any hydration arrangement was posed as an array named connectivity matrix. The connectivity matrix and the economical balance were written in computer code in order to carry out the optimization procedure. The optimization started from a minimum amount of water, and stepwise increasing levels of hydration were evaluated. The best value of this combinatorial search was retained. The optimum arrangement was pure countercurrent in most of cases considered.